2008
DOI: 10.1007/s00253-008-1549-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient secretion of Bacillus subtilis lipase A in Saccharomyces cerevisiae by translational fusion to the Pir4 cell wall protein

Abstract: Both the secretion and the cell surface display of Bacillus subtilis lipase A (Lip A) in Saccharomyces cerevisiae was investigated using different domains of the cell wall protein Pir4 as translational fusion partners. LipA gene minus its leader peptide was fused inframe in two places of PIR4 to achieve cell wall targeting, or substituting most of the PIR4 sequence, after the signal peptide and the Kex2 processed subunit I of Pir4 to achieve secretion to the growth medium. Expression of the recombinant fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In our group, fusion with the cell wall protein Pir4 [10] has been used for the expression of Bacillus sp. BP-7 xylanase A [11], Bacillus subtilis lipase A [13] and the VP8* fragment of the rotavirus spike protein [12], all of them using this particular yeast strain as host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our group, fusion with the cell wall protein Pir4 [10] has been used for the expression of Bacillus sp. BP-7 xylanase A [11], Bacillus subtilis lipase A [13] and the VP8* fragment of the rotavirus spike protein [12], all of them using this particular yeast strain as host.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 β was expressed in S. cerevisiae BY4741 using the signal peptide and pro domain of the Pir4 cell wall protein [10], previously used to express and secrete into the medium a Bacillus sp.BP-7 xylanase A [11], the VP8* fragment of rotavirus capsid protein [12] and Bacillus subtilis lipase A [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, previous studies, in which ScPir4 has been linked to Bacillus sp. proteins, lipase A or xylanase A for display in S. cerevisiae , revealed that while 100% of ScPir4-xylanase was cell-bound, only 40% of the lipase A appeared to be anchored to the cell wall [3], [4]. Moreover, when a ScPir4 variant was used, which lacks the aforementioned functionally important Cys residues, only 12% of either protein was found to be cell bound.…”
Section: Resultsmentioning
confidence: 99%
“…This allows the fusion protein to form disulphide bonds with Aga1, another α-agglutinin subunit, which is in turn covalently linked to the cell wall through GPI anchor. The third system, called Protein Internal Repeat (or Pir)-CWP, is unrelated to the former and permits the covalent linkage of fusion proteins both to cell wall β-1,3 glucans and to structural proteins via disulfide bonds [3], [4]. Finally, an alternative, but rarely employed system consists of the non-covalent adsorption of an enzyme to the cell surface via interactions with a Chitin Binding Module (CBM) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Pir4 has already been successfully used as a fusion partner for the targeting of other proteins of interest such as xylanase A from Bacillus sp. BP-7 (Andrés et al 2005), the VP8* fragment from the rotavirus spike protein (Andrés et al 2006) and lipase A from Bacillus subtilis (Mormeneo et al 2008) either to the cell wall or to the culture medium.…”
Section: Introductionmentioning
confidence: 99%